Strategic Value Creation: The Pathway to Sustainable Industrial Competitiveness - Arabi, Nahla G. A. (International Review of Management and Marketing, 2025)
This research investigates how capabilities for creating value (VCC) drive enduring strategic edge (SCA) in Egypt’s industrial sector. Through rigorous quantitative analysis of 324 responses from senior managers, the study examines critical dimensions of VCC—financial analysis, economic performance, and market and customer insights—The findings reveal that market and customer insights emerge as the most powerful predictors of enduring strategic edge, highlighting the critical importance of aligning business strategies with evolving customer needs in today’s dynamic marketplace. Notably, capabilities for creating value account for 51.2% of the variation in enduring strategic edge, underscoring their fundamental role in enhancing organizational competitiveness. The research further emphasizes the strategic imperative of integrating sustainability practices into core business operations to maintain competitiveness in increasingly environmental, social, and governance (ESG) -conscious markets. For industrial leaders and policymakers, this study offers actionable, evidence-based recommendations to strengthen competitive positioning through strategic financial management, customer relationship enhancement, and sustainability initiatives—ensuring long-term success while aligning with broader societal priorities.